Didactics in higher education: a look from educational journals between 1931 and 1944 - Oliveira Reis, Karina Cassia [UNESP]; Michelli de Castro, Rosane [UNESP]; Rangel de Almeida, Jonas [UNESP] (Edipucrs-editora Univ Pucrs, 2022)
The article presents elements for analysis and possible research on the field of Didactics in Higher Education from educational journals that circulated in Brazil between 1931 and 1944. To do this, it was necessary to select 28 articles from collaborators of magazines that deal with some aspects of Didactics. The analyzes were performed in the light of the contributions of Garcia (2000), mainly, regarding the moment of constitution and institutionalization of the field of Didactics. Didactics, in Brazil, was based on the theories arising from psychological tests, mainly, with regard to moments of Garcia (2000) between 1930 and 1950, a time when Brazilian teaching was undergoing effervescent discussions and changes about which teaching methods were better to be applied and, in general, with childhood, mainly with the first years of life - Child Psychology.
Keywords: education; idactics; educational journals